Yoga and Naturopathy Approach in the management of Ankylosing Spondylitis: A Case Report - S, NaveenKumar; MR, Monicaasun; S, Gokulakrishnan; N, Mangaiyarkarasi; S, Prashanth (Indian Journal of Integrative Medicine, 2024)
Ankylosing spondylitis (AS) is an inflammatory rheumatic disease that affects the axial skeleton, instigating characteristic of back pain, stiffness which leads to structural and functional impairments also decreases the quality of life. There is no specific cause identified for Ankylosing spondylitis. Which set off health care professionals to face difficulties towards its cure; This study aims to describe the Yoga and Naturopathy system of approach in patients with ankylosing spondylitis. They evolve as treatment strategies for AS to manage the symptoms and its severity. A 23 year old male previously identified with AS, got admitted for 10 days in the inpatient ward, After the intervention period the patient showed improvement in the post assessments, the sit and reach test score were improved from 8 to 11 inches, and pain in the visual analogue scale was reduced from 7 (moderate) to 3 (Good), which also showed improvement in the patient’s Quality of life by mean of Evaluating Ankylosing Spondylitis Quality of Life (EASI-QoL) score was reduced 61/80 to 32/80. By these results we conclude Yoga and Naturopathy system of medicine can be effective in the management of patients with AS as a supportive or standalone treatment choice for managing the symptoms and severity of the disease.